Committee deliberation and gender differences in influence - Jonas Radbruch; Amelie Schiprowski (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
This paper provides empirical evidence on the aggregation of information in committees. We analyze unique data from the decision-making process of hiring committees within a large private company. In the hiring process, committee members first conduct independent one-to-one interviews and give individual recommendations before deliberating on a collective hiring decision. We find that committees' final hiring decisions are systematically less aligned with the initial recommendations of women than with those of men, even though women and men are equally qualified and experienced. This disparity in influence is strongest when recommendations exhibit high disagreement and when a single woman deliberates with two men. The estimated distribution of influence reveals that almost all men are more influential than the median woman. We offer suggestive evidence that these findings have implications for the effectiveness of gender quotas.
Keywords: D71; J16; M51; 330; Committee Decision-Making; Gender Differences; Hiring